A historical review of WWER RPV embrittlement issues. (1st January 2011) - Brumovsky, Milan; Nikolaev, Vladimir
The paper tries to describe the history of the radiation effects study in WWER type reactor pressure vessels – from their design, manufacturing and operation point of view. The paper shows the time evolution and also institutions that were and are included in this research and development study. Main effort has been concentrated on development and realisation of steels and welding joint with low susceptibility to radiation damage as neutron fluences on reactor pressure wall in WWER type reactors are relatively high.